Assessment of fish catch in some mangrove patches in Taklong Island. Nueva Valencia Guimaras six months after oil spill. - Epalan, Ruby Gay S. (2012.)
M/T Solar I spilled 2M liters of bunker fuel last August 11, 2006 on southern Guimaras coastline and struck a toll on the ecology of the marine reserve. One of the habitats that were affected during the oil spill was the mangrove areas in Taklong Island, Guimaras. Mangroves provide shelter and food for the diverse faunal community that inhabit within the mangrove area itself and to the adjacent coastal waters. This animal community includes different kind of fish that serve as a source of food and economic stability to the nearby residents. In this study, fish catch in some mangrove patches in Taklong Island, Nueva Valencia, Guimaras were identified and compared to other studies. The sampling was done every two weeks by using gill nets with 2x2 mesh size. T-test was used to compare sampling means before and after oil spill. Results show there is no significant difference in the number of individual fishes average weight between the pre-spill and 6 months after oil spill catch. However, mean number of species observed and the fish length recorded showed significant difference between the two samples. And there is a significant difference in the number of individual fishes, number of fishes, average weight and average lenght between the pre-spill and 43 months after oil spill catch.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Mangroves -- Taklong Island